Characteristics of Cotton, Polyester and Rayon Fabrics Coated with Acetobacter xylinum - Syazwani Mustafa Kamal, Amira; Iqbal Misnon, Mohd; Nazarudin Zakaria, Mohd; Ismail AB Kadir, Muhammad; Rozi Ahmad, Mohd (International Journal of Engineering and Technology, 2018)
Bacterial cellulose (BC) was applied as coating material on three types of fabrics which were cotton, polyester and rayon. The characteristics of the coated BC fabrics were determined and the ability of BC to act as coating material was investigated. BC was produced using Gram-negative bacteria, Acetobacter xylinum, under static batch fermentation conditions of coconut water-based media containing 8.0% sugar, 0.5% ammonium sulphate and 0.1% acetic acid. The analyses were done after purification of the coated fabrics with 1% of sodium hydroxide and hot air dried at 130Â°C. The bursting strength, impact penetration and water vapor permeability of the uncoated and coated BC samples were investigated. The Cotton-BC (CottBC) samples had the highest thickness, followed by the Rayon-BC (RayBC) and Polyester-BC (PolyBC) samples. All the coated BC samples obtained lower percentage of water impact than uncoated samples where the PolyBC samples had the lowest percentage. Besides, the BC itself had lower water percentage (131.76%) compared with all the uncoated fabrics. During the water vapor permeability test, the coated BC samples released less water vapor than the uncoated samples. Nevertheless, peeling off between the BC and Polyester fabrics was observed for PolyBC samples, showing that the adhesion between them is weak. The findings of this research disclosed that the performance of BC coating to fabric are good for cotton and rayon fabrics but not for the polyester fabric.Â